The Relationship between Lead Exposure and Depression in Online Ojek Drivers in West Jakarta in 2022 - Johannes Hudyono; Ernawati Tamba; Lisa Silvia (Jurnal MedScientiae, 2023)
Lead is a naturally occurring element found in trace amounts in the earth's crust. Lead can be toxic to humans and animals, causing health effects. This study used an observational analytic design with a cross-sectional design technique, samples were taken using a non-probability sampling method using an accidental sampling technique, using the Lameshow formula with a total of 100 online motorcycle taxi drivers as subjects. Lead exposure in subjects showed no exposure/mild was not found, moderate, high, very high levels of lead exposure were found in 7 (7.0%), 35 (35.0%), 58 (58.0%) respondents respectively. Subjects with mild, moderate, severe and very severe depression were found in 27 (57.4%), 14 (29.8%), 2 (4.3%), 4 (8.5%) respondents respectively. Obtained subjects with moderate lead exposure with depression, high with depression, very high with depression 3 (3.0%), 16 (16.0%), 28 (28.0%) respondents respectively. Moderate lead exposure was not depressed, high was not depressed, 4 (4.0%), 19 (19.0%), 30 (30.0%) respondents respectively, and the relationship between lead exposure and the incidence of depression obtained results p<0.061, Conclusion in this study there was no significant relationship between lead exposure and the incidence of depression in online motorcycle taxi drivers in West Jakarta in 2022.